2022
DOI: 10.3389/fnut.2022.821404
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Isolated From Porcine Bone Soup Ameliorated Dextran Sulfate Sodium-Induced Colitis and Regulated Gut Microbiota in Mice

Abstract: Daily foods contain a great number of self-assembled nanoparticles (NPs) which were incidentally produced during food processing. These food incidental NPs can directly access the human gastrointestinal tract in high frequency and large quantities. Limited reports were focused on whether and how these food incidental NPs affected the gastrointestinal tissues and gut microbiota. In the present study, bone soup and its NPs both significantly ameliorated colitis symptoms in dextran sulfate sodium (DSS)-induced mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The family Prevotellaceae and the genus Alloprevotella were relatively enriched in CAip group. Consistent with our results, the genus Alloprevotella was demonstrated to be lower in DSS-induced experimental colitis, which was generally considered to be short chain fatty acid producer and its abundance was inversely correlated with inflammation ( 45 , 46 ). Collectively, the alleviative effects of CA on the experimental colitis might be attributed to its gut microbiota modulation activity.…”
Section: Discussionsupporting
confidence: 91%
“…The family Prevotellaceae and the genus Alloprevotella were relatively enriched in CAip group. Consistent with our results, the genus Alloprevotella was demonstrated to be lower in DSS-induced experimental colitis, which was generally considered to be short chain fatty acid producer and its abundance was inversely correlated with inflammation ( 45 , 46 ). Collectively, the alleviative effects of CA on the experimental colitis might be attributed to its gut microbiota modulation activity.…”
Section: Discussionsupporting
confidence: 91%
“…At the genus level, after supplementation of TP, the abundance of Muribaculaceae, Ileibacterium, Lactobacillus, Alloprevotella, and Bifidobacterium was notably elevated and the abundance of Lachnospiraceae was decreased in UC mice; it has been reported that most of these bacteria in UC patients were significantly disturbed . In addition, Muribaculaceae and Bifidobacterium were demonstrated to be potentially beneficial for relieving inflammation and facilitating immunocompetence in colitis mice Ileibacterium and Alloprevotella, the groups of bacteria associated with SCFAs, have been proved to modulate systemic inflammation .…”
Section: Discussionmentioning
confidence: 98%
“…38 In addition, Muribaculaceae and Bifidobacterium were demonstrated to be potentially beneficial for relieving inflammation and facilitating immunocompetence in colitis mice. 39 Ileibacterium and Alloprevotella, the groups of bacteria associated with SCFAs, have been proved to modulate systemic inflammation. 40 Similarly, our results indicated that the cecal contents of SCFAs were elevated by the intake of TP in UC mice.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Lactobacillus has the potential to alleviate inflammation and enhance immune function in mice suffering from DSS-induced colitis. 59,60 In the DSS group, there was a significant decrease in the abundance of Lactobacillus , whereas intervention with HF06, HF05, and MIXL resulted in a significant increase in Lactobacillus levels. Notably, MIXL exhibited a more pronounced effect in increasing the abundance of Lactobacillus compared to HF06 and HF05.…”
Section: Discussionmentioning
confidence: 99%